The Cas6e ribonuclease is not required for interference and adaptation by the E. coli type I-E CRISPR-Cas system. Issue 12 (26th May 2015) - Semenova, Ekaterina; Kuznedelov, Konstantin; Datsenko, Kirill A.; Boudry, Pierre M.; Savitskaya, Ekaterina E.; Medvedeva, Sofia; Beloglazova, Natalia; Logacheva, Maria; Yakunin, Alexander F.; Severinov, Konstantin
Abstract: CRISPR-Cas are small RNA-based adaptive prokaryotic immunity systems protecting cells from foreign DNA or RNA. Type I CRISPR-Cas systems are composed of a multiprotein complex (Cascade) that, when bound to CRISPR RNA (crRNA), can recognize double-stranded DNA targets and recruit the Cas3 nuclease to destroy target-containing DNA. In the Escherichia coli type I-E CRISPR-Cas system, crRNAs are generated upon transcription of CRISPR arrays consisting of multiple palindromic repeats and intervening spacers through the function of Cas6e endoribonuclease, which cleaves at specific positions of repeat sequences of the CRISPR array transcript. Cas6e is also a component of Cascade. Here, we show that when mature unit-sized crRNAs are provided in a Cas6e-independent manner by transcription termination, the CRISPR-Cas system can function without Cas6e. The results should allow facile interrogation of various targets by type I-E CRISPR-Cas system in E. coli using unit-sized crRNAs generated by transcription.